The U.S. Budget Deficit and the Foreign Exchange Value of the Dollar - Melvin, Michael; Schlagenhauf, Don; Talu, Ayhan (The Review of Economics and Statistics, 1989)
This paper presents and estimates a simple model of real exchange rate determination that includes the expected future U.S. federal budget deficit as a determinant. The model is applied to the real value of the dollar versus the mark, yen, and pound over the period June 1974-October 1987. The estimates suggest that rapid increases in the expected future deficit in the early 1980s contributed to a rapid appreciation of the dollar. The fall in the value of the dollar in the spring of 1985 appears to be due to a fall in the expected budget deficit. Copyright 1989 by MIT Press.